Tea Consumption and Risk of Bladder Cancer: A Dose-Response Meta-Analysis - Weng, Hong; Zeng, Xian-Tao; Li, Sheng; Kwong, Joey S. W.; Liu, Tong-Zu; Wang, Xing-Huan (Frontiers in Physiology, 2017)
Background and Objective: Controversial results of the association between tea (black tea, green tea, mate, and oolong tea) consumption and risk of bladder cancer were reported among epidemiological studies. Thus, we performed a meta-analysis of observational studies to investigate the association. Methods: We searched the PubMed and Embase for studies of tea consumption and bladder cancer that were published in any language up to March, 2016. Cohort or case-control studies were included in the meta-analysis. All statistical analyses were performed in Stata 12.0 software. Results: Totally, 25 case-control studies including 15 643 cases and 30 795 controls, and 7 prospective cohort studies including 1807 cases and 443 076 participants were included in our meta-analysis. The overall odds ratio (OR) with corresponding 95% confidence interval (CI) between tea consumption and bladder cancer risk was 0.96 (95% CI 0.86 to 1.06) (in a comparison of highest versus lowest category). Specific analysis for black tea, green tea, and mate yielded similar results. The dose-response analysis showed the summary OR for an increment of 1 cup/day of tea consumption was 1.01 (95% CI 0.97 to 1.05). Conclusion: Results of this meta-analysis suggested that there was no significant association between tea consumption and bladder cancer risk.